2022
DOI: 10.1002/lary.30284
|View full text |Cite
|
Sign up to set email alerts
|

The Role of PARP‐1 and NF‐κB in Bile‐Induced DNA Damage and Oncogenic Profile in Hypopharyngeal Cells

Abstract: Objectives/Hypothesis We recently documented that acidic bile, a gastroesophageal reflux content, can cause invasive hypopharyngeal squamous cell carcinoma, by inducing widespread DNA damage and promoting nuclear factor kappa B (NF‐κB)‐related oncogenic molecular events. Poly or adenosine diphosphate (ADP)‐ribose polymerase‐1 (PARP‐1), a sensitive sensor of DNA damage, may interact with NF‐κB. We hypothesized that PARP‐1 is activated in hypopharyngeal cells (HCs) with marked DNA damage caused by acidic bile, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 61 publications
1
2
0
Order By: Relevance
“…Interestingly, in this study, no more severe DNA damage was observed in sh-PARP1 cells treated with HQ (Figure ). This phenomenon was also observed in a study conducted by Doukas PG et al on DNA damage caused by Bile . This may indicate that although knockdown PARP1 inhibits DNA damage caused by HQ through the PARP1 and NF-κB pathways, the attempt to regulate DNA damage through these pathways becomes meaningless because of the loss of the role of PARP1 in DNA damage repair.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Interestingly, in this study, no more severe DNA damage was observed in sh-PARP1 cells treated with HQ (Figure ). This phenomenon was also observed in a study conducted by Doukas PG et al on DNA damage caused by Bile . This may indicate that although knockdown PARP1 inhibits DNA damage caused by HQ through the PARP1 and NF-κB pathways, the attempt to regulate DNA damage through these pathways becomes meaningless because of the loss of the role of PARP1 in DNA damage repair.…”
Section: Discussionsupporting
confidence: 65%
“…This phenomenon was also observed in a study conducted by Doukas PG et al on DNA damage caused by Bile. 44 This may indicate that although knockdown PARP1 inhibits DNA damage caused by HQ through the PARP1 and NF-κB pathways, the attempt to regulate DNA damage through these pathways becomes meaningless because of the loss of the role of PARP1 in DNA damage repair. These results indicate that inappropriate inhibition of PARP1 is not beneficial for the repair of DNA damage caused by HQ and that appropriately activating PARP1 and inhibiting the NF-κB pathway can aid in DNA damage repair and cell survival.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the saliva bile salt concentration was predictive of the severity of LPR [18]. The toxicity of bile salts on laryngopharyngeal tissue was confirmed in experimental studies that supported a potential carcinogenic role of bile acids in laryngeal squamous cell carcinoma [19]. According to the literature, pepsin and bile acids may be considered important etiological factors for upper aerodigestive tract mucosa inflammation and related symptoms and findings.…”
Section: Physiology 21 Gastroduodenal Enzymesmentioning
confidence: 81%